TESS Giants Transiting Giants. IV. A Low-density Hot Neptune Orbiting a Red Giant Star - Samuel K. Grunblatt; Nicholas Saunders; Daniel Huber; Daniel Thorngren; Shreyas Vissapragada; Stephanie Yoshida; Kevin C. Schlaufman; Steven Giacalone; Mason Macdougall; Ashley Chontos; Emma Turtelboom; Corey Beard; et al. (The Astronomical Journal, 2024)
Hot Neptunes, gaseous planets smaller than Saturn (∼3–8 R _⊕ ) with orbital periods less than 10 days, are rare. Models predict this is due to high-energy stellar irradiation stripping planetary atmospheres over time, often leaving behind only rocky planetary cores. Using our TESS full-frame-image pipeline giants in conjunction with Keck/HIRES radial velocity measurements, we present the discovery of TIC365102760 b, a 6.2 R _⊕ (0.55 R _J ), 19.2 M _⊕ (0.060 M _J ) planet transiting a red giant star every 4.21285 days. The old age and high equilibrium temperature yet remarkably low density of this planet ( ${ρ }_{p}={0.58}_{-0.20}^{+0.30}{ρ }_{{\rm{J}}}$ ) suggest that its gaseous envelope should have been stripped by high-energy stellar irradiation billions of years ago. The present-day planet mass and radius suggest the atmospheric stripping was slower than predicted. Unexpectedly low stellar activity and/or late-stage planet inflation could be responsible for the observed properties of this system. Further studies of this system with more precise photometry in multiple passbands will be capable of revealing more details of this planet’s atmosphere.